Single‐Molecule Force Spectroscopy Trajectories of a Single Protein and Its Polyproteins Are Equivalent: A Direct Experimental Validation Based on A Small Protein NuG2. Issue 22 (27th December 2016) - Lei, Hai; He, Chengzhi; Hu, Chunguang; Li, Jinliang; Hu, Xiaodong; Hu, Xiaotang; Li, Hongbin
Abstract: Single‐molecule force spectroscopy (SMFS) has become a powerful tool in investigating the mechanical unfolding/folding of proteins at the single‐molecule level. Polyproteins made of tandem identical repeats have been widely used in atomic force microscopy (AFM)‐based SMFS studies, where polyproteins not only serve as fingerprints to identify single‐molecule stretching events, but may also improve statistics of data collection. However, the inherent assumption of such experiments is that all the domains in the polyprotein are equivalent and one SMFS trajectory of stretching a polyprotein made of n domains is equivalent to n trajectories of stretching a single domain. Such an assumption has not been validated experimentally. Using a small protein NuG2 and its polyprotein (NuG2)4 as model systems, here we use optical trapping (OT) to directly validate this assumption. Our results show that OT experiments on NuG2 and (NuG2)4 lead to identical parameters describing the unfolding and folding kinetics of NuG2, demonstrating that indeed stretching a polyprotein of NuG2 is equivalent to stretching single NuG2 in force spectroscopy experiments and thus validating the use of polyproteins in SMFS experiments. Abstract : Direct experimental validation : Using optical tweezers, the equivalency of single‐molecule force spectroscopy trajectories of a single domain and its polyprotein is directly demonstrated on a small protein NuG2. The results not only lay a solid foundation for atomic force microscopy experiments using polyproteins, but also pave the way for other force spectroscopy methods to make use of and benefit from polyproteins.